ACCUMULATION OF CHEMICAL COMPOUNDS IN SOIL AND DISEASES OCCURING IN HUMANS (Scientific journal of the Fergana State University, 2025)
This article describes diseases that occur among people as a result of soil pollution. Chemical elements and compounds of various sources and their harmful aspects are identified in the composition of soils. The issues of impact on human health are widely covered.